REAPING THE AFFORDANCES AND CONSTRAINTS OF CANVAS-DRIVEN ASYNCHRONOUS ONLINE DISCUSSION BOARDS (AODBs) - Sofarini, Anisa; Salsabila, Vina Aini (English Review: Journal of English Education, 2024)
Abstract: Asynchronous online discussion board (AODB) has turned into a crucial tool for online and blended learning, as well as some in-class teaching contexts, in higher education (HE). Despite not being initially designed for teaching, it is now prominently featured as a learning autonomy promoter. This research is henceforth crucial due to the dearth of comprehensive assessments of how a technology enables lecturers to tote out the AODB-related activities. Employing technology affordance framework helped shape this study’s discoveries. Via the 16-week observations on the five lecturers’ AODBs in Canvas LMS, this study put together four supporting features, enabling this study to capture lecturers’ efforts to set up AODBs for pedagogical process. There are instruction pages, settings, search entries for authors, replies and likes. These features led this study to lump together the interview data from three lecturers into four affordances of Canvas-mediated AODB (consisting of collaboration, flexibility, knowledge record, and monitoring and assessment) and two constraints (mobile accessibility and usability for grading). The disclosure of Canvas-mediated AODBs’ affordances and constraints may introduce some brand-new details to the realm of discussion in education. Even so, further study scrutinizing various platforms and employing a variety of lecturer profiles is highly encouraged in order to result in a wider range of facts regarding AODB in HE.